ANALISIS PERLAKUAN AKUNTANSI ASET BIOLOGIS BERDASARKAN PSAK NO 69 PADA PT. SRIWIJAYA PALM OIL PALEMBANG - F Febransyah; Suci Alinda (JURNAL KOMPETITIF, 2020)
The aim of this research is to find out the accounting treatment of biological assets at PT. Sriwijaya Palm Oil Palembang. Data collection techniques used in this study were interviews and documentation. Research subjects are PT. Sriwijaya Palm Oil Palembang. The research objects are journals, balance sheet / financial position reports and other supporting documents. Research instruments with the variable Biological Asset Accounting Treatment, the indicators are recognition, measurement, presentation and disclosure. Data analysis techniques using qualitative descriptive analysis methods by data reduction, data presentation and drawing conclusions and verification. Based on the results of research and discussion, it is known that accounting treatment of biological assets at PT. Sriwijaya Palm Oil Palembang, namely recognition of biological assets as Fixed Assets and agricultural products as inventories, measurement of biological assets and inventories based on acquisition prices, presentation of biological assets on the Balance Sheet at the Non-Current Asset heading and Inventory at the Balance Sheet at the Current Asset post and all operational activities and Company policies are disclosed in the Notes to the Financial Statements. The accounting treatment of biological assets based on PSAK No. 69 which is the adoption of IAS 41, namely the recognition of biological assets as biological assets themselves and agricultural products as Inventories, measurement of biological assets based on fair value after deducting the estimated cost of sales (fair value less to cost point of sell), presentation of biological assets on Balance sheet in Non-current Assets and Inventory items in the balance sheet in Current Assets and all of the company's operations and policies are disclosed in the Notes to the Financial Statements. Keywords: Biological Assets